An assessment of the small enterprise technology upgrading program (setup) the case of the FPRDI lumber dryer - Garcia, Carolyn Marie C.; Posadas, Roger (Quezon City University of the Philippines Diliman, 2010)
The Small Enterprise Technology Upgrading Program (SETUP) of the DOSt is a strategy to encourage MSMEs to adopt technology innovations that can improve their operations, and boost productivity and competitiveness. This study aims to find out whether SETUP's goal of increasing the competitiveness of MSMEs in the furniture sector had been attained by assessing the impact of the FTLD as a technological intervention. The study has the following objectives : 1) To determine and assess the outcomes of the FTLD as a technological intervention; 2) To provide an understanding of the various causal relationships resulting from the intervention; and 3) To identify areas and recommend measures for improvement of the SETUP program. The framework for the evaluation followed a simple model that focused on causation and attempted to show that the activities provided by SETUP were the reasons why change occurred for the individuals receiving the intervention. The framework lays out how the intervention (inputs) has affected final outcomes by analysing the causal chain, from inputs to impacts. From 2003 to 2007, the period covered by the study, eight furniture firms were granted financial assistance to acquire the FTLD by the SETUP NPMO. Support activities such as site assessment, supervision of the construction of the dryer, and training on kiln drying were conducted by FPRDI under the FHIST project. A log frame for the FHIST project was created for this study. Increased productivity and improvement in product quality of furniture firms plus the necessary conditions of a strong marketing support program and efficiently managed MSMEs lead to increased competitiveness. Outputs that will bring about changes in productivity are the equipment and technologies adopted by SETUP beneficiaries. Productivity benefits of the FTLD for six or 75 percent of the firms were not realized. Of the six firms, five were micro scale and only one was small. At the time of the study, the FTLDs in these firms were operating at an average of only 3 percent to 40 percent of total capacity. In contrast, the FTLDs in the remaining two firms were operating at above average industry rates.
Differences in outcomes can be attributed to factors both internal and external to the project. These are : a flawed assessment of the local market during the proposal stage, firms' lack of resources to cover costs associated with increased production, owner's inadequate entrepreneurial ability, difficulty in accessing marketing support for MSMEs, and the global downturn experienced in the latter years of the decade 2000-2010. The following recommendations should be considered : There should be a more realistic assessment of the market for those who wish to avail of SETUP assistances; SETUP should consider including the technical assessment by the RDIs during the early phase of the proposal evaluation; SETUP should consider building a stronger collaboration with DTI; the study also revealed the need to standardize the design of the FTLD.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: Small business -- Philippines; Technological innovations; Furniture industry and trade -- Philippines; Small enterprise technology upgrading program (setup).; FPRDI lumber dryer